Experimental Study on Wind Erosion Resistance and Strength of Sands Treated with Microbial-Induced Calcium Carbonate Precipitation - Zhaoyu Wang; Nan Zhang; Jinhua Ding; Chen Lu; Yong Jin (Advances in Materials Science and Engineering)
Wind erosion phenomenon is commonly encountered in desert areas, which is harmful to engineering constructions and environment. This study proposed an innovative microbial-induced calcium carbonate precipitation (MICP) technique to reinforce sands for mitigating natural hazards caused by the wind erosion. A series of small-scale laboratory experiments were performed to evaluate wind erosion resistance of MICP-treated sands with different treatment cycles. The spraying method was used to treat sand specimens, and unconfined compression (UCC) strength tests were also conducted to assess the performance of the MICP technique. Experimental results revealed that the bulk density of treated sand was slightly increased with the number of MICP treatment cycles. Additionally, the wind erosion rate of treated sands was significantly decreased, and the UCC strength was increased (maximum to 4 MPa) with the number of treatment cycles, which was mainly attributed to the bonding effect from the microbial-induced CaCO3 crystals among sand particles based on the scanning electron microscopy (SEM) analyses. Such effect also facilitated to form a hard protection layer on top of the sand specimen in order to improve the wind erosion resistance of MICP-treated sands. This technique provides an alternative method to mitigate and prevent the aggravation of desertification.